PERBANDINGAN UJI EFEKTIVITAS ANTIDIABETES TERHADAP LUMATAN DAUN SALAM (Syzygium polyanthum Wight) DAN DAUN UBI JALAR UNGU (Ipomoea batatas L.) PADA MENCIT TAHUN 2021 - Angga Nugraha Sanjaya; Bunga Rimta Barus (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2021)
Background: Agustin, Diana parmaning Comparison of antidiabetic effectiveness tests against crushed bay leaves (Syzygium polyanthum W) and purple sweet potato leaves (Ipomoea batatas L) in mice in 2021. (Supervised by: apt. Bunga Rimta Barus, S.farm.,M.Si ) Diabetes mellitus is a constant metabolic infection portrayed by an expansion in blood glucose levels that can be treated with customary medication got from plants. One illustration of a plant that can decrease blood glucose levels is inlet leaf and purple yam leaf which contain flavonoids to bring down blood glucose by expanding cell affectability to insulin and expanding insulin in pancreatic cells. To decide the impact of the blend of cove leaf concentrate and yam leaf in bringing blood glucose levels contrasted down with glibenclamide. The trial study utilized 15 mice which were initiated by alloxan and partitioned into 5 gatherings. Gathering 1 (negative control) CMC Na 1%, bunch 2 (positive control) glibenclamide at a portion of 0.65 mg/kgBB, bunch 3 a solitary cove leaf remove at a portion of 100 mg/kgBB, bunch 4 a solitary purple yam leaf separate at a portion of 200 mg/kg. kgBB, bunch 5 blend of straight leaf separate at a portion of 150 mg/kgBB and purple yam leaf extricate at a portion of 150 mg/kgBB. Extraction utilizing maceration strategy with 96% ethanol dissolvable. From the aftereffects of the investigation, every treatment bunch encountered a lessening in blood glucose levels. Of the 5 treatment gatherings, the best decrease in blood glucose levels was the three mix gatherings. Among the three mix gatherings, the mix portion of 150 mg/kgBB of inlet leaves and 150 mg/kgBB of purple yam leaves was the best contrasted with glibenclamide in bringing down blood glucose levels.Conclusion: The blend of sound leaf concentrate and purple yam leaf has a more successful impact on bringing down blood glucose levels than glibenclamide and its single concentrate.